Observation of crack initiation zone in brick masonry couplets under compression using X-ray microfocus computed tomography and digital image correlation. (7th December 2020) - Shetty, Naveen; Livitsanos, Georgios; Verstrynge, Els; Aggelis, Dimitrios G.; Hemelrijck, Danny Van; Balen, Koen Van; Wevers, Martine
The constituent materials of masonry include different brick and mortar types with various properties. The difference in the stiffness properties of these materials influence the observed failure modes under compression. The general theory of the failure mechanisms in brick masonry under compressive loading relies on the difference between the relative elastic modulus of brick and mortar. The aim of this paper is to visually examine the above theory about the behaviour of masonry under compression using a high-resolution X-ray micro-CT scanner. Additionally, full-scale couplets have been tested under compression with the application of stereo-vision digital image correlation (DIC). The failure progression in masonry which evolves from the initiation of micro cracks, over the propagation into macro cracks has been clearly evidenced. Overall, the results from DIC positively confirm the observation from X-ray micro-CT.